Prawne regulacje funkcjonowania samorządu terytorialnego w aspekcie efektywności nadzoru oraz kontroli sądowoadministracyjnej - Nogieć-Karwot, Edyta (Studia Prawa Publicznego, 2023)
The article presents an analysis of legal regulations concerning supervisory institutions as a key element in how local government functions. The effectiveness of supervision institutions is analyzed on the basis of legal regulations concerning bodies supervising the activities of local government. Exercising legal supervision contributes to restoring the state of affairs consistent with law, if it has been violated, thus presenting statutory supervisory measures at the disposal of supervisory authorities. Ongoing supervision of voivodes and regional accounting chambers, as a matter of principle, is related to examining the legality of the legislative activity of the decision-making bodies of local government units, therefore the article discusses the process of supervisory proceedings related to the issuance of a supervisory decision by the supervisory authority. In order to exercise supervision more effectively, in addition to appropriate legislative changes and the elimination of existing legal loopholes, in the author’s opinion, it is necessary to deﬁne the principles of cooperation between supervisory authorities and other entities, including developing and agreeing on procedures for the mutual exchange of information. In addition, the actions taken by prosecutors, who, using their statutory powers, ﬁle numerous complaints to administrative courts against resolutions of local government units are also indicated. However, there is a complete lack of knowledge on the part of the supervisory authorities in this regard. The text recapitulates the results of the audit carried out by the Supreme Audit Office which concerned the supervision of voivodes over lawmaking by local government units in 2017–2019. The analysis of the subject of legal regulations relating to the exercise of supervision provides the basis for the author to formulate de lege ferenda postulates and to present the proposed directions of changes.